FROM TRADITIONAL CLASSROOM COMMUNICATION TO COMMUNICATION IN THE VIRTUAL SPACE - Florentin Remus MOGONEA; FLORENTINA MOGONEA (Universitaria Publishing House, Craiova, 2020)
The study aims to address the issue of communication based on a twofold analysis, encompasing face-to-face and virtual communication, the latter being mediated by the new communication technologies. The general framework of the current digital society, as well as the specific context of the Coronavirus pandemic have imposed the implementation of new technologies in the teaching process; daily routine activities are now taking place not only directly, but also exclusively online or in the blended learning mode. We intend to outline this evolution, mainly focusing on the current situation, which we shall analyze taking into consideration the possibilities of the Romanian schools to meet the demands of online activities, as they are facing the specific challenges of this type of communication. The review of recent studies and reports allows us to diagnose the ways of setting up online communication and interaction at the level of the pre-university education system, and based on our own teaching experience, we shall be able to perform a critical analysis of the advantages and disadvantages of online communication in the academic environment, more specifically within the pre-service teacher training programme.